Sodium-dependent organic anion transporter (Slc10a6−/−) knockout mice show normal spermatogenesis and reproduction, but elevated serum levels for cholesterol sulfate. Issue 179 (May 2018) - Bakhaus, Katharina; Bennien, Josefine; Fietz, Daniela; Sánchez-Guijo, Alberto; Hartmann, Michaela; Serafini, Rosanna; Love, Charles C.; Golovko, Andrei; Wudy, Stefan A.; Bergmann, Martin; Geyer, Joachim
Highlights: An Slc10a6 ko mouse model was established and used for reproductive phenotyping and steroid profiling. Slc10a6 ko mice were fertile, produced normal litter sizes, and had normal spermatogenesis and sperm vitality. Male Slc10a6 ko mice showed significantly elevated serum levels for cholesterol sulfate. Elevated cholesterol sulfate may have an effect on skin and lung, both organs having high Soat expression. Abstract: The sodium-dependent organic anion transporter SOAT (gene name SLC10A6 in man and Slc10a6 in mice) is a plasma membrane transporter for sulfated steroids, which is highly expressed in germ cells of the testis. SOAT can transport biologically inactive sulfated steroids into specific target cells, where they can be reactivated by the steroid sulfatase (STS) to biologically active, unconjugated steroids known to regulate spermatogenesis. Significantly reduced SOAT mRNA expression was previously found in different forms of impaired spermatogenesis in man. It was supposed that SOAT plays a role for the local supply of steroids in the testis and consequently for spermatogenesis and fertility. Thus, an Slc10a6 −/− Soat knockout mouse model was established by recombination-based target deletion of the Slc10a6 gene to elucidate the role of Soat in reproduction. However, the Slc10a6 −/− knockout mice were fertile, produced normal litter sizes, and had normal spermatogenesis and sperm vitality. This phenotype suggests that the loss of Soat can be compensated in the knockout mice or that Soat function is not essential for reproduction. In addition to reproductive phenotyping, a comprehensive targeted steroid analysis including a set of 9 un-conjugated and 12 sulfo-conjugated steroids was performed in serum of Slc10a6 −/− knockout and Slc10a6 +/+ wildtype mice. Only cholesterol sulfate, corticosterone, and testosterone (only in the males) could be detected in considerable amounts. Interestingly, male Slc10a6 −/− knockout mice showed significantly higher serum levels for cholesterol sulfate compared to their wildtype controls. As cholesterol sulfate has a broader impact apart from the testis, further analysis of this phenotype will include other organs such as skin and lung, which also show high Soat expression in the mouse.